Pembelajaran Berbasis Kurikulum Merdeka pada Program Keahlian Akuntansi dan Keuangan Lembaga Kelas XI di SMK Negeri 1 Banyudono - Diman, Vinna Idamtus Silmi; Syah, Muhammad Fahmi Johan (Buletin Literasi Budaya Sekolah, 2023)
The rapid development of the world of education has encouraged changes in the curriculum in Indonesia, one of which is the Merdeka Curriculum "independent learning". This study aims to describe the implementation, benefits, and obstacles that occur in learning based on the Merdeka Curriculum in the Accounting and Finance Expertise Program for class XI institutions at SMK Negeri 1 Banyudono. The data collection techniques used are observation, interviews, and documentation involving teachers and students. The data analysis technique uses data collection, data reduction, data presentation and conclusion drawing or data verification. The results of this study indicate that the implementation of Independent Curriculum-based learning in the Accounting and Finance Expertise Program for class XI institutions at SMK Negeri 1 Banyudono has provided significant benefits. Teachers and students feel freedom in developing learning materials that suit student needs. Not only that, but the Merdeka Curriculum also provides opportunities for students to develop independence in learning and contribute to skills such as public speaking, creativity, and broader horizons. However, there are also obstacles faced, namely the difficulty of getting a good internet network.